MODELING THE FORMATION OF FLUORIDE NITROGEN-RICH HOT SPRINGS IN THE WATER – CRYSTALLINE ROCK SYSTEM - S. Kh. Pavlov; K. V. Chudnenko; A. V. Khromov (Геодинамика и тектонофизика, 2020)
Physicochemical interactions in the water – porphyrite system in conditions of formation of nitrogen-rich hot springs were studied using computer simulation. Compositions of model solutions during such interactions are determined by a combined influence of the compositions of primary and secondary rock minerals. In the investigated interaction range, the solution actively processes large quantities of the primary rock in favor of secondary minerals, while dissolved components are accumulated in small amounts in the solution itself, and therefore the salinity is low. The intervals of the formation of hydrosilicate, bicarbonate and sulfate sodium solutions are clearly distinguished in the process of irreversible hydrolytic transformation of porphyrite. In a certain range of interactions, the compositions of the model solutions are well comparable with the compositions of natural high-fluoride hot springs. Nitrogen-rich hot springs are strongly influenced by meteogenic factors detectable by detailed and/or sufficiently long-term observations. In deep and surface conditions, the model solutions and natural hot springs considerably differ in composition. Differences are hardly noticeable in the behavior of cations, fluorine, chlorine, and sulfates, but are strongly manifested in changes in the quantities of carbon and silicon compounds and transformations of their forms. These transformations explain the hitherto incomprehensibly different ratios of hydrocarbonate and carbonate ions and hydrosilicate ions and silicic acid both in different hydrothermal sources and in different analyses of hot springs in nature. The development of thermal waters in crystalline rocks is related to two types of heterogeneities that are typical for the development of geological bodies. The first heterogeneity is the disturbed continuity of rocks in fault zones of various orders, due to which groundwater can penetrate into these structures. The uneven distribution of anionic elements in space is another heterogeneity predetermining the groundwater composition and, in particular, accumulation of fluorine, which is confirmed by the results of geological studies, as well as the study of the formation of high-fluoride groundwaters (including thermal water) in various geological structures.